Perencanaan Perkerasan Lentur Jalan Raya Dengan Metode Analisis Komponen Bina Marga 1987 (Studi Kasus Ruas Jl. Raya Banjarsari-Cerme Kabupaten Gresik) - Dandy Nugroho; Akhmad Andi Saputra; Muchammad Dian Nurdianto (Wahana Teknik, 2020)
Banjarsari Highway is an arterial road in the primary road network system that connects Surabaya, Krian, Sidoarjo, Mojokerto and Lamongan areas. Banjarsari-Cerme Highway uses flexible pavement consisting of basic soil layer, bottom foundation layer, top foundation layer and surface layer. The arrangement of these layers is generally used on roads that have a fairly high volume of traffic. Over time, the number of vehicles passing is increasing and eventually causing road damage in a relatively short period of time. Therefore, it is very important to make road improvements in accordance with the Average Daily Traffic Volume (VLHR) and the composition of passing vehicles. This study will calculate and plan the type of pavement that is feasible according to the age of the planned plan. To supporting this study, several data are needed such as: traffic volume data, rainfall data, CBR data, and secondary data obtained from the Public Works Office and Gresik Regency Transportation Office. From the data obtained, it is then processed and analyzed on the calculation of pavement bending new roads with Bina Marga standards. Planning in this study uses flexible pavement analysis in accordance with the Guidelines for Thick Planning of Pavement Pavement with Component Analysis Method (SKBI-2.3.26.1987) and combined with AASHTO method 1993. The results of this study are: (1) The average daily traffic (LHR) based on the age of the 10-year plan on Banjarsari-Cerme road is 29,418 vehicles per day. (2) The thickness of the planned bending pavement on Banjarsari-Cerme road in Gresik regency based on the analysis method of the 1987 Bina Marga SKBI component of 97.50 cm with the following details: a) Surface layer (surface course) used Laston MS-744 with a thickness of 17.50 cm with details of a wear layer AC-WC 7.50 cm thick and foundation layer AC-BC as thick as 10 cm. b) The base course is used 100% CBR 100% grade with a thickness of 35 cm. c) The bottom foundation layer (subbase course) is used sirtu (class B) CBR 50% with a thickness of 45 cm. Keywords: Average Daily Traffic, Bending Pavement Layer, Component Analysis and AASHTO Method.